2009
DOI: 10.1007/s11423-009-9131-z
|View full text |Cite
|
Sign up to set email alerts
|

Improving course evaluations to improve instruction and complex learning in higher education

Abstract: Recent research has touted the benefits of learner-centered instruction, problembased learning, and a focus on complex learning. Instructors often struggle to put these goals into practice as well as to measure the effectiveness of these new teaching strategies in terms of mastery of course objectives. Enter the course evaluation, often a standardized tool that yields little practical information for an instructor, but is nonetheless utilized in making high-level career decisions, such as tenure and monetary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 16 publications
0
30
0
2
Order By: Relevance
“…In a follow-up study, Frick, Chadha, Watson and Zlatkovska (2010) found that if students agreed that they experienced ALT, then they were about five times more likely to be independently judged at a high level of mastery of course objectives by their instructors. Perhaps more important, they were 10 times more likely to be assessed as low masters of course objectives by their instructors if they did not agree that they experienced ALT.…”
Section: Internal Factorsmentioning
confidence: 99%
“…In a follow-up study, Frick, Chadha, Watson and Zlatkovska (2010) found that if students agreed that they experienced ALT, then they were about five times more likely to be independently judged at a high level of mastery of course objectives by their instructors. Perhaps more important, they were 10 times more likely to be assessed as low masters of course objectives by their instructors if they did not agree that they experienced ALT.…”
Section: Internal Factorsmentioning
confidence: 99%
“…For improving the quality of student learning, even though there are a number of surveybased models that consider teacher centric and/or institution centric processes (Chapman and Henderson, 2010;Frick et al, 2010), at the detail level, to the best of our knowledge, application of CI models is relatively sparse. Penn State's IMPROVE model, which is an expansion of Shewhart (1939)/Deming (1986) 'plan-do-check [study]-act' model, demonstrates how to facilitate problem solving, decision making, and process improvement in higher education (Kelly, 2010).…”
Section: Attainment Of Student Learning Objectives Through 'Ci'mentioning
confidence: 99%
“…For instance, instructors could benefit from the access to a teaching model template which supports the design and delivery of problem-solving instruction using selected instructional design theories such as the FPOI (First Principles of Instruction) (Merrill, 2012). Studies done by other researchers (Frick, Chadha, Watson, & Zlatkovska, 2010;Lo & Hew, 2017) have also suggested that the use of the First Principles of Instruction can improve students' motivation and learning when compared with other forms of instruction.…”
Section: Implications Of the Findingsmentioning
confidence: 99%